Protein C Antigen Levels in Major Abdominal Surgery: Relationships to Deep Vein Thrombosis, Malignancy and Treatment with Stanozolol - Blamey, S L; Lowe, G D O; Bertina, R M; Kluft, C; Sue-Ling, H M; Davies, J A; Forbes, C D (Thrombosis and Haemostasis, 1985)
Activated protein C is a potent inhibitor of coagulation, and familial protein C deficiency has been associated with recurrent venous thrombosis. We have investigated protein C antigen levels in patients undergoing major elective abdominal surgery, to determine their relationships to postoperative deep vein thrombosis (DVT), malignancy, and preoperative treatment with intramuscular or oral stanozolol. Preoperative and postoperative protein C levels were not significantly different in patients with and without DVT (detected by 125I-fibrinogen leg scans), nor in patients with and without malignancy. In a placebo group (n = 26), a significant fall in protein C was maximal on the first postoperative day and persisted for 7 days. In a group given intramuscular stanozolol, 50 mg on the preoperative day (n = 23) stanozolol shortened the duration of the postoperative fall in protein C, but did not prevent DVT. In a group given oral stanozolol, 10 mg/day for 2 weeks before and 1 week after operation (n = 11), stanozolol significantly increased protein C levels prior to surgery, hence maintaining protein C at pretreatment levels after surgery. The effect of this regimen on the incidence of DVT is under study.
Keywords: Protein C; Deep vein thrombosis; Surgery; Malignancy; Anabolic steroids